Different Attitudes And Interpretations Toward Social Justice In Western Philosophical Thought - Teshaboev Mukhiddin Marifovich (Genius Journals, 2023)
In this article, the basis of Social Justice as an idea is based on the requirement to treat all people equally. Accordingly, it is clarified that no one should be discriminated against on the basis of social, religious and cultural prejudices, and that everyone should have such minimum resources that they can create their own concept of "good life".
Keywords: Category; truth; idea of justice; model of justice